2009
DOI: 10.1259/bjr/40733553
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flat-panel-detector-based CT and multidetector-row CT in automated volumetry of pulmonary nodules using an anthropomorphic chest phantom

Abstract: This study evaluates the accuracy and reproducibility of an experimental flat-panel-detector-based CT scanner (fp-CT) in comparison with those of a 64-slice multidetector row CT (MDCT) in automated pulmonary nodule volumetry. An anthropomorphic chest phantom with 31 spherical nodules (nodule diameters of 2.94-10.01 mm; volumes of 13.24-524.97 mm(3)) was scanned both with an amorphous silicon-based fp-CT scanner, using various tube current and kilovoltage settings, and with a conventional MDCT scanner. Automate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Some in vitro studies have been performed in which artificial nodules were placed at known locations in a thoracic phantom without pulmonary vessels [13][14][15]. Some of these studies were based on older generation CT scanners [13,16].…”
mentioning
confidence: 99%
“…Some in vitro studies have been performed in which artificial nodules were placed at known locations in a thoracic phantom without pulmonary vessels [13][14][15]. Some of these studies were based on older generation CT scanners [13,16].…”
mentioning
confidence: 99%
“…Flat-panel scanners outperform multi-detector scanners in pulmonary nodule volumetry, especially in small nodules (< 5 mm) [ 82 – 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Volumetry is less performant for small nodules [ 10 , 13 , 16 , 18 , 21 , 25 , 28 , 29 , 31 , 36 38 , 40 , 41 , 45 , 48 51 , 53 , 55 , 56 , 60 , 63 , 70 , 72 , 74 , 78 , 79 , 81 , 82 , 89 , 92 , 93 , 95 101 ], explained mainly by partial volume effects, and is considered unreliable for nodules < 5 mm in diameter [ 60 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prionas et al 32 reached similar conclusions using simulated tumors. Marten et al 33 observed a greater tendency to underestimate nodule volume for smaller nodules. This collective evidence may be relevant, since it indicates that measurements of smaller volumes are less accurate than those of larger ones.…”
Section: Discussionmentioning
confidence: 96%